Adult immunization practices, challenges and opportunities in Central America and the Caribbean: Advisory board proceedings. Issue 7 (30th December 2022) - Naranjo, Laura; Domínguez, Elidia; Rodriguez, Carlos; Chandler, Reynaldo; Belén Arauz, Ana; Barahona de Mosca, Itza; Hernández, Telma; Coto, Fernando; Ramirez Chavez, Jorge; Sandoval, Nancy; Castrejón, María Mercedes; Leal, Ingrid; et al.
ABSTRACT: As individuals age, they become increasingly prone to infectious diseases, many of which are vaccine-preventable diseases (VPDs). Adult immunization has become a public health priority in the modern era, yet VPDs vaccination rates for adults are low worldwide. In Central America and Caribbean, national recommendations and vaccination practices in adults differ across countries, and adult vaccination coverage data are limited. An advisory board comprised infectious disease experts, pulmonologists, geriatricians, occupational health, and public health professionals for Central America and Dominican Republic was convened to: a) describe adult immunization practices in these countries; b) discuss challenges and barriers to adult vaccination; and c) find strategies to increase awareness about VPDs. The advisory board discussions reflect that national immunization guidelines typically do not include routine vaccine recommendations for all adults, but rather focus on those with risk factors. This is the case for influenza, pneumococcal, and hepatitis B immunizations. Overall, knowledge lacks about the VPD burden among health-care professionals and the general public. Even more, there is insufficient information on vaccinology for students in medical schools. Actions from the responsible authorities – medical schools and scientific societies which can advocate for vaccination and a better knowledge in vaccinology – can help address these issues. A preventive medicine culture in the workplace may contribute to the advancement of public opinion on vaccination. Promoting vaccine education and research could be facilitated via working groups formed by disease experts, public and private sectors, and supranational authorities, in an ethical and transparent manner.